PENERAPAN MULTIMEDIA PEMBELAJARAN ILMU PENGETAHUAN ALAM FUNGSI ORGAN TUBUH MANUSIA DAN HEWAN BERBASIS FLSAH UNTUK KELAS V SEKOLAH DASAR - Candra Dewi (Universitas Muhammadiyah Ponorogo, 2017)
The purpose of this study is to improve the learning outcomes of science of human body and animal 5th grade animal organ function through the application of interactive model based on flash. This form of research is a classroom action research of 2 cycles. Each cycle consists of 4 stages: planning, action implementation, observation and reflection. The subjects of the study were the 5th graders of SDN 05 Dagen as many as 20 students. Data collection techniques use observation, interview, test and documentation. Data analysis technique used is interactive analysis model which has three component that is data reduction, data presentation and conclusion drawing. Based on the results of research that is with the implementation of learning in the cycle I and cycle II can be concluded that there is an increase in learning outcomes by applying interactive multimedia based flash. This can be demonstrated by the increased ability of students from before and after action.